Transcriptomics and proteomics revealed the psychrotolerant and antibiotic-resistant mechanisms of strain Pseudomonas psychrophila RNC-1 capable of assimilatory nitrate reduction and aerobic denitrification - Zhao, Yuanyi; Min, Hongchao; Luo, Kongyan; Zhang, Ruijie; Qian Chen; Chen, Zhaobo (Science of the Total EnvironmentScience of the Total Environment, 2022)
Aerobic denitrification has been proved to be profoundly affected by temperature and antibiotics, but little is known about how aerobic denitrifiers respond to temperature and antibiotic stress. In this study, the nitrate reduction performance and the intracellular metabolism by a psychrotolerant aerobic denitrifying bacteria, named Pseudomonas psychrophila RNC-1, were systematically investigated at different temperatures (10 degrees C, 20 degrees C, 30 degrees C) and different sulfamethoxazole (SMX) concentrations (0 mg/L, 0.1 mg/L, 0.5 mg/L, 1.0 mg/L, and 5.0 mg/L). The results showed that strain RNC-1 performed satisfactory nitrate removal at 10 degrees C and 20 degrees C, but its growth was significantly inhibited at 30 degrees C. Nitrate removal by strain RNC-1 was slightly promoted in the presence of 0.5 mg/L SMX, whereas it was significantly suppressed with 5.0 mg/L SMX. Nitrogen balance analysis indicated that assimilatory nitrate reduction and dissimilatory aerobic denitrification jointly dominated in the nitrate removal process of strain RNC-1, in which the inhibition effected on assimilation process was much higher than that on the aerobic denitrification process under SMX exposure. Further transcriptomics and proteomics analysis revealed that the psychrotolerant mechanism of strain RNC-1 could be attributed to the up-regulation of RNA translation, energy metabolism, ABC transporters and the over-expression of cold shock proteins, while the down-regulation of oxidative phosphorylation pathway was the primary reason for the deteriorative cell growth at 30 degrees C. The promotion of nitrate reduction with 0.5 mg/L SMX was related to the up-regulation of amino acid metabolism pathways, while the down-regulation of folate cycle, glycolysis/gluconeogenesis and bacterial chemotaxis pathways were responsible for the inhibition effect at 5.0 mg/L SMX. This work provides a mechanistic understanding of the metabolic adaption of strain RNC-1 under different stress, which is of significance for its application in nitrogen contaminated wastewater treatment processes.